2017
DOI: 10.1002/tea.21405
|View full text |Cite
|
Sign up to set email alerts
|

The effects of visualizations on linguistically diverse students’ understanding of energy and matter in life science

Abstract: Although extensive research has shown the educational value of different types of interactive visualizations on students’ science learning in general, how such technologies can contribute to English learners’ (ELs) understanding of complex scientific concepts has not been sufficiently explored to date. This mixed‐methods study investigated how interactive dynamic and static visualizations embedded in web‐based inquiry instruction can support ELs and non‐ELs in developing a coherent understanding of energy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 83 publications
2
18
0
Order By: Relevance
“…Because the DuPont Model is integrative in nature and involves diagramming the DuPont Model on a whiteboard, students are able to visualize the connections between the financial statements at one end of the model and the financial ratios at the other end, thereby seeing the accounting concepts as a single set of interrelated concepts. These results provide evidence of the benefits of visualization as a means for helping students “integrate information” (Zhang & Linn, 2011, p. 1177), a practice that has proven to be effective in other settings where educators face similar challenges as those in accounting education (Chang & Linn, 2013; Rau, 2017; Rumanová & Drábeková, 2019; Ryoo & Bedell, 2017; Vitale, McBride, & Linn, 2016).…”
Section: Discussionmentioning
confidence: 79%
“…Because the DuPont Model is integrative in nature and involves diagramming the DuPont Model on a whiteboard, students are able to visualize the connections between the financial statements at one end of the model and the financial ratios at the other end, thereby seeing the accounting concepts as a single set of interrelated concepts. These results provide evidence of the benefits of visualization as a means for helping students “integrate information” (Zhang & Linn, 2011, p. 1177), a practice that has proven to be effective in other settings where educators face similar challenges as those in accounting education (Chang & Linn, 2013; Rau, 2017; Rumanová & Drábeková, 2019; Ryoo & Bedell, 2017; Vitale, McBride, & Linn, 2016).…”
Section: Discussionmentioning
confidence: 79%
“…Out of the 14 articles published at Journal of Research in Science Teaching (top journal in the field), 2 studies used video games (Israel et al, ; Sadler et al, ), 10 integrated simulations (Bell & Trundle, ; Chao et al, ; Chen et al, ; Gerard, Spitulnik, & Linn, 2010; Hmelo‐Silver et al, ; Jaakkola et al, ; Mulder, Bollen, de Jong, & Lazonder, ; Plass et al, ; Quellmalz, Timms, Silberglitt, & Buckley, ; Scalise & Clarke‐Midura, ), and 2 used interactive dynamic visualizations (Ryoo & Bedell, ; Ryoo & Linn, ). The video games targeted topics such as cell anatomy and functions, genes and inheritance (Israel et al, ), and one was in the form of a virtual biotechnology lab (Sadler et al, ).…”
Section: Seven Emergent Technologies Used In Science Educationmentioning
confidence: 99%
“…Through extensive research over the last 20 years, the KI framework has been shown to be effective in helping students evaluate multiple ideas presented in dynamic visualizations and in facilitating student learning across science topics, including thermodynamics (Davis, ), global climate change (Raes, Schellens, & De Wever, ), chemistry (Chiu & Linn, ), and ecosystems (Clark, Touchman, Martinez‐Garza, Ramirez‐Marin, & Drews, ). Recent studies provide evidence that the KI framework has the potential to engage both ELLs and non‐ELLs in various science practices to understand and link abstract scientific concepts, such as constructing explanations, using evidence for argumentation, and obtaining, evaluating, and communicating information (e.g., Ryoo & Bedell, ; Ryoo, Toutkoushian, & Bedell, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For instance, Molenaar, Sleegers, and van Boxtel () found that students who were prompted to elicit ideas about metacognition strategies engaged in more conversations about planning their learning tasks and monitoring their progress when compared to students who received direct explanations during collaborative learning. ELLs also need to negotiate how to integrate different views into written explanations to represent their understanding of the target concepts with their partners (e.g., Levy, ; Ryoo & Bedell, ; van Joolingen, de Jong, & Dimitrakopoulou, ). Such processes can help ELLs use “the language of the science classroom” (Lee, Quinn, & Valdés, p. 221) in multiple ways to articulate and communicate their ideas.…”
Section: Conceptual Frameworkmentioning
confidence: 99%